Future Challenges to Security and Politics in Iraq - Ashti, Murtaza Akbari; Suhail , Mohammad Baqir (The International and Political Journal, 2025)
This research addresses the security and military challenges facing Iraqi politics, significantly influenced by internal dynamics and regional and international interactions. These challenges emerged prominently following the 2003 American occupation of Iraq, exacerbating political and security divisions and leading to economic and social deterioration. In 2014, challenges intensified with the rapid expansion of the terrorist organization ISIS and its control over parts of Iraqi territory, posing a significant threat to the existence of the Iraqi state itself. Moreover, neighboring regional powers intervened in Iraq with their own interests, complicating Iraq’s efforts to maintain sovereignty and independence. Iraq's national security has been greatly affected by internal factors such as corruption and political instability, alongside external factors such as regional interventions and international security challenges. Achieving comprehensive national security requires holistic strategies that effectively address these factors. Key recommendations include enhancing international and regional cooperation to combat terrorism and ensure regional stability. It is also essential to improve the military capabilities of the Iraqi armed forces and strengthen partnerships with international forces to enhance technological and intelligence capabilities. Additionally, reforming security agencies and promoting good governance to combat corruption and enhance transparency and accountability in public affairs are crucial. Security and military challenges in Iraq necessitate multidimensional strategies that respond to both internal and external challenges in a balanced manner, contributing to the establishment of a strong and stable Iraqi state that preserves its sovereignty and national security.